Inseminating dose and water volume applied to the artificial fertilization of Steindachneridion parahybae (Steindachner, 1877) (Siluriformes: Pimelodidae): Brazilian endangered fish - Sanches, Eduardo Antônio [UNESP]; Caneppele, Danilo; Okawara, Renan Yoshiharu; Damasceno, Danielle Zanerato [UNESP]; Bombardelli, Robie Allan; Romagosa, Elizabeth (FapUNIFESP (SciELO), 2016)
The Steindachneridion parahybae is an endangered catfish from Brazil and strategies applied for gametes optimization are necessary. The aim of this study was to assess inseminating doses and water volume upon the fertilization, hatching rates and percentage of normal larvae in S. parahybae. Was used a randomized design in factorial scheme (4×4) with four inseminating doses: 1.0×104, 1.0×105, 1.0×106, 1.0×107 spermatozoa oocyte-1 and four volumes of water: 1, 35, 65 and 95mL of water g-1 of oocytes. The combination of doses and volumes were performed in triplicates (n=48). Each incubator (1.5L of useful volume) with 1g of oocytes was considered as an experimental unit. Significant interaction between inseminating doses and volumes of water to the values of the fertilization rates and quadratic effect of doses and volume for the values of hatching rates were observed. The doses and volumes did not influence the percentage of normal larvae (87.70±5.06%). It is recommended the use of 5.5×106 spermatozoa oocyte-1 and 1mL of water g-1 of oocytes during in vitro fertilization procedure. These results allowed us to develop new biotechnological strategies applied to the conservation of S. parahybae.
Keywords: Artificial reproduction; Freshwater fish; Oocytes; Sperm; Surubim-do-Paraíba